Results of Cytogenetic and Molecular Cytogenetic Studies in Relapce/Refractory of Multiple Myeloma - Andreieva, Svitlana; Korets, Kateryna (Innovative Biosystems and Bioengineering, 2018)
Background. Multiple myeloma (MM) – a tumor of the lymphoid tissue, which is characterized by low proliferative activity of abnormal cells and a wide range of acquired chromosomal aberrations that play a leading role in predicting the course of the disease. Accumulation of new data in the relapsed/refractory of MM will make it possible to understand the nature of the formation of cloning insensitive to chemotherapy (CT), to predict the effectiveness of therapy, which will further improve the individualization of treatment for each patient. Objective. The aim of the study is to determine the peculiarities of chromosomal aberrations of abnormal clones of bone marrow (BM) cell in relapsed/refractory of MM by standard cytogenetic and molecular cytogenetic investigations. Methods. Analysis of BM cells chromosomal abnormalities in relapsed/refractory of MM for 62 patients with MM was performed. Slides of metaphase chromosomes were prepared according to standard procedure after cultivating during 24 or 96 h in the medium without stimulation. Results. Clonal chromosomal abnormalities were formed, complexity structure of karyotypes with clone structures was shown. In structural rearrangements, derivative chromosomes (34.9%) and balanced translocations (23.2%) were dominated at cytogenetic procedure. By molecular cytogenetic (i-FISH) investigation chromosomal abnormalities were detected in 26.7% cases. Del(17)(p13.1) was registered in 22.0%. Aberrations involving IGH were fixed in 5.7%. The atypical signal distribution determined by i-FISH may indicate another possible mechanism for the evolution of an abnormal clone. Conclusions. The cytogenetic peculiarities of the formation of abnormal BM cell clones in relapse/refractory of MM formations, discovered by us, supplement the understanding of the biological features of the disease and contribute to the outline of further tasks for the study of genetic aberrations in MM.